Successive mycelial subculturing decreased lignocellulase activity and increased ROS accumulation in Volvariella volvacea - Zhao, Fengyun; Liu, Xiaoxia; Chen, Chao; Cheng, Zhihong; Wang, Wenpei; Yun, Jianmin (Frontiers in Microbiology, 2022)
Strain degradation is a common problem in many artificially-cultivated edible mushrooms. As a fungus with poor tolerance to low-temperature, Volvariella volvacea cannot delay its degradation by long-term low temperature storage like other fungi, so its degradation is particularly severe, which hinders industrial applications. Periodic mycelial subculture is a common storage method for V. volvacea, but excessive subculturing can also lead to strain degeneration. After 20 months of continuous subculturing every 3 days, V. volvacea strains S1–S20 were obtained, and their characteristics throughout the subculture process were analyzed. With increasing number of subculture, the growth rate, mycelial biomass, the number of fruiting bodies and biological efficiency gradually decreased while the production cycle and the time to primordium formation was lengthened. Strains S13–S20, obtained after 13–20 months of mycelial subculturing, also lacked the ability to produce fruiting bodies during cultivation experiments. Determination of reactive oxygen species (ROS) content as well as enzyme activity showed that decreased lignocellulase activity, along with excessive accumulation of ROS, was concomitant with the subculture-associated degeneration of V. volvacea. Reverse transcription polymerase chain reaction (RT-PCR) was eventually used to analyze the gene expression for lignocellulase and antioxidant enzymes in subcultured V. volvacea strains, with the results found to be consistent with prior observations regarding enzyme activities. These findings could form the basis of further studies on the degeneration mechanism of V. volvacea and other fungi.